CRYPTOCURRENCIES AND CENTRAL BANK DIGITAL CURRENCIES (CBDCS): OPPORTUNITIES AND RISKS - Bakoeva Gulbakhor (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
This paper explores the similarities and differences between cryptocurrencies and central bank digital currencies (CBDCs), examining how both forms of digital money shape the global financial landscape. It highlights the opportunities these innovations offer for improving payment systems, financial inclusion, and cross-border transactions, while also addressing associated risks such as cybersecurity, volatility, and regulatory uncertainty. Drawing on recent empirical studies and global developments, the article provides an analytical overview of how decentralized and centralized digital currencies coexist and compete within the modern economy.